2020
DOI: 10.1007/s00330-020-07271-0
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography semi-automated lung volume quantification in SARS-CoV-2-related pneumonia

Abstract: Objectives To evaluate a semi-automated segmentation and ventilated lung quantification on chest computed tomography (CT) to assess lung involvement in patients affected by SARS-CoV-2. Results were compared with clinical and functional parameters and outcomes. Methods All images underwent quantitative analyses with a dedicated workstation using a semi-automatic lung segmentation software to compute ventilated lung volume (VLV), Ground-glass opacity (GGO) volume (GGO-V), and consolidation volume (CONS-V) as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 26 publications
(42 reference statements)
2
18
0
Order By: Relevance
“…Their semi-automatic software showed a strong negative correlation between P/F ratio or hypercapnia, expression of hypoxia, and analyzed CT volumes. [108] Moreover, the Dense-UNet used by Mergen et al further confirmed the previously described positive correlations about CRP and leukocytes. Authors underlined the negative correlation between percentage of opacity (PO) or percentage of high opacity (PHO, consolidations) with SO 2 as an additional demonstration that patients in need for supplemental oxygen have a higher proportion of involved lungs [109].…”
Section: Ai In the Stratification And Definition Of Severity And Complications Of Covid-19 Pneumonia At Chest Ctsupporting
confidence: 67%
“…Their semi-automatic software showed a strong negative correlation between P/F ratio or hypercapnia, expression of hypoxia, and analyzed CT volumes. [108] Moreover, the Dense-UNet used by Mergen et al further confirmed the previously described positive correlations about CRP and leukocytes. Authors underlined the negative correlation between percentage of opacity (PO) or percentage of high opacity (PHO, consolidations) with SO 2 as an additional demonstration that patients in need for supplemental oxygen have a higher proportion of involved lungs [109].…”
Section: Ai In the Stratification And Definition Of Severity And Complications Of Covid-19 Pneumonia At Chest Ctsupporting
confidence: 67%
“…In other words, the most useful prognostic CT sign in predicting the outcome of COVID-19 patients was the expression of global lung involvement, regardless of the type of alteration and the consolidation density of the images. Although some recent papers [25][26][27] described some results on quantification based on open-source software for semi-automated pulmonary segmentation, in our experience, the visual analysis of lung involvement proved to be a quick, easy-to-use and reliable method for the evaluation and quantitation of lung involvement. This procedure can also be used also in an emergency scenario, independently of sophisticated, different, and still not fully comparable software-based methods for the interpretation of CT images.…”
Section: Discussionmentioning
confidence: 84%
“…The Fleischner Society issued a consensus statement in order to explore the best application of imaging, primarily CT, for the evaluation and risk stratification of patients [10], acknowledging that, in addition to supporting diagnosis, CT has also revealed its usefulness for providing diagnostic information. This approach requires the quantification of abnormalities that currently can be reached through visual analysis [19][20][21][22][23], or more recently using a software-based assessment [24][25][26][27] or, possibly in the future, artificial intelligence (A.I.) [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, pulmonary function impairment prior to hospitalisation predicts COVID-19 disease outcomes in sarcoidosis [ 25 ] and other chronic comorbid pulmonary conditions have been associated with poor outcome in COVID-19 such as COPD and ILD [ 26 , 27 , 28 , 29 ]. Ippolito et al [ 30 ], using quantitative CT analysis, found that disease severity and need for invasive ventilation was correlated with measures of lung volume. If lung volume measurements and pulmonary function can predict severity, it may be that static lung volumes and/or diffusing capacity abnormalities are not the consequence of COVID-19 disease severity, but that pre-existing abnormality contributes to COVID-19 disease severity.…”
Section: Discussionmentioning
confidence: 99%